Review of the Monograph: Kolosov I. V. the History of Legal Consequentialism: The Effectiveness of Law - Mukienko, Igor (Տիգրան Մեծ)
This article presents a review of the monograph “The History of Legal Consequentialism: The Effectiveness of Law”. I. V. Kolosov‟s monograph is a comprehensive study of the use of the principle of utility and other principles aimed at achieving a certain effect, i.e., doctrines that are based on the fact that legally significant actions are approved or disapproved depending on their potential to achieve a result. The subject of this monograph is specific ideas about the effective implementation of legal activities within the framework of these doctrines, including in the context of lawmaking and law enforcement, which determines its practical significance. I. V. Kolosov‟s monograph is valuable for modern legal science from the point of view of its systematic, scientific, and representative analysis of scientific sources. The scientific significance of the monograph is expressed in conclusions, generalisations and proposals. I. V. Kolosov‟s research organically combines both a theoretical analysis of the content of legal doctrines of various time periods, from the standpoint of general philosophical, axiological, historical, general and comparative legal aspects, and practical conclusions and proposals regarding the possibilities of legal activities, taking into account the theoretical framework of legal consequentialism.
Keywords: Book review